Investigating the Chaperone Properties of a Novel Heat Shock Protein, Hsp70.c, from Trypanosoma brucei - Adélle Burger; Michael H. Ludewig; Aileen Boshoff (Journal of Parasitology Research)
The neglected tropical disease, African Trypanosomiasis, is fatal and has a crippling impact on economic development. Heat shock protein 70 (Hsp70) is an important molecular chaperone that is expressed in response to stress and Hsp40 acts as its co-chaperone. These proteins play a wide range of roles in the cell and they are required to assist the parasite as it moves from a cold blooded insect vector to a warm blooded mammalian host. A novel cytosolic Hsp70, from Trypanosoma brucei, TbHsp70.c, contains an acidic substrate binding domain and lacks the C-terminal EEVD motif. The ability of a cytosolic Hsp40 from Trypanosoma brucei J protein 2, Tbj2, to function as a co-chaperone of TbHsp70.c was investigated. The main objective was to functionally characterize TbHsp70.c to further expand our knowledge of parasite biology. TbHsp70.c and Tbj2 were heterologously expressed and purified and both proteins displayed the ability to suppress aggregation of thermolabile MDH and chemically denatured rhodanese. ATPase assays revealed a 2.8-fold stimulation of the ATPase activity of TbHsp70.c by Tbj2. TbHsp70.c and Tbj2 both demonstrated chaperone activity and Tbj2 functions as a co-chaperone of TbHsp70.c. In vivo heat stress experiments indicated upregulation of the expression levels of TbHsp70.c.